Description of Palaces in Abbasi Poetry - Tharwat Ahmad Wahdan (My University, 2003)
The effect of different levels of manufactured organic fertilizer and chemical fertilizer on the growth and yield of three wheat varieties was studied. The expirement was conducted during the year 2001-2002 growing season at Biet Qad Agriculture Expirmental Station near Jenin. Five levels of the organic fertilizer were used (100, 300, 400, 500 and 600 kg / dunum. Another chemical treatment was used with consists of adding 35 kg / dunum superphosphate and 25 kg/ dunum ammonium sulfate, in addition acontrol treatment was involved a total of 7 fertilizer treatment and 3 varieties were arranged in a completely randomized design of four replicare for each treatment . the following mesurement were taken before harvest. Plant hight, Tiller number, number of fruiting tellers. After harvesting: the total weight, grain weight and the straw weight were calculated. Sample seeds were taken from each replicate for determining the level of nitrogen, phosphorous and potassium. The result showed a significiant effect of organic fertilizer treatment over the chemical fertilizer the effect was mainly signficiant on total weight, plant length, number of tillers and the straw weight. Asiginficiant difference was also exhibited by the different varities , mainly for plant height where the hitia variety showed high plant height over the other tow varieties. The mineral content of the grain was not effect the different fertilizer treatments.

موضوع هذا البحث هو "وصف القصور في الشعر العباسي" ويتناول دراسة هذا الفن الشعري الجديد، كما يتناول علاقته بالأغراض الشعرية الأخرى، وتضمَّنت هذه الرسالة مقدِّمة تحدثت فيها عن كيفية اختياري لهذا الموضوع والصعوبات التي واجهتني أثناء كتابته وكيف تمكَّنت من تجاوزها. جاءت هذه الدراسة في بابين، خصصت الأول منهما للدراسة الموضوعية واشتمل هذا الباب على أربعة فصول، أمّا الأول فقد خصصته للحديث عن الملامح العمرانية القديمة والحضارة الإنسانية الأولى، وتحدثت في الفصل الثاني عن عوامل ازدهار التطور الحضاري وأسبابه في العصر العباسي، وأما الفصل الثالث فقد خصصته للحديث عن أهم شعراء القصور في العصر العباسي؛ البحتري، علي بن الجهم، وعبد الله بن المعتز وأبي نواس وأشجع السلمي والصنوبري، وتحدثت في هذا الباب أخيراً عن أهم القصور العباسية والتي حصرتها مصادر الدراسة الأدبية والتاريخية في ستة عشر قصراً. وخصصت الباب الثاني للدراسة الفنية وقد توزعته ثلاثة فصول، خصصت الأول منها للحديث عن الصور الجدارية والصور التراثية، ثم انتقلت إلى الحديث عن الملامح الأدبية والفنية في شعر وصف القصور، واختتمت حديثي في هذا الباب عن دراسة في الألفاظ والمعاني والتشكيل الإيقاعي للموسيقا.
وصف القصور في الشعر العباسي